309 Tralokinumab demonstrated a consistent safety profile with up to 42 months of treatment in moderate-to-severe atopic dermatitis: including adverse events of special interest. (25th January 2023) - Reich, Kristian; Simpson, Eric; Langley, Richard; Warren, Richard B; Costanzo, Antonio; Saeki, Hidehisa; Almgren, Peter; Gjerum, Le; Carlsson, Anna; Gooderham, Melinda; Pinter, Andreas; De Bruin Weller, Marjolein; et al.
Abstract: As atopic dermatitis (AD) is a chronic and potentially life-long disease, it is important to determine the long-term safety of new treatments. Tralokinumab, which specifically targets interleukin-13, is approved in Europe, Canada and the United States for the treatment of adults with moderate-to-severe AD. During the initial 12–16 week placebo-controlled treatment period of Phase 2 and 3 trials, tralokinumab was well-tolerated with an overall frequency of adverse events (AEs) similar to the placebo. An ongoing open-label extension trial, ECZTEND (NCT03587805), is assessing the safety and efficacy of tralokinumab up to 5 years after parent trials (PT). To report an interim safety analysis of patients treated with tralokinumab for up to 42 months (≤ 1 year in PT and ≤ 2.5 years in the open-label extension ECZTEND), including AEs of special interest (AESI). In ECZTEND, moderate-to-severe AD patients who completed the previous tralokinumab PT received subcutaneous tralokinumab 300 mg every 2 weeks after a 600 mg loading dose; topical corticosteroid use was optional. All AEs were recorded, coded, and classified by severity, causality and outcome. AESIs were predefined in PT based on areas of safety interest for monoclonal antibodies in AD, including eye disorders (e.g. conjunctivitis), skin infections requiring systemic treatment, eczema herpeticum and malignancies diagnosed after dosing. Event rates are presented as the number of events (nE) per 100 patient-years of exposure (PYE). All AEs described were treatment-emergent AEs, defined as AEs reported after the first dosing of the study drug. As of 30 April 2021, the interim safety analysis included 1442 patients from the PT ECZTRA 1, 2, 3, 4, 5 and 7 who had received ≥1 dose of tralokinumab in ECZTEND, with 121.0 weeks mean exposure time on tralokinumab [median 131.5 weeks (IQR 83.4–161.8); min 0.0, max 186.4 weeks]. Total exposure time in ECZTEND was 2446.2 PYE. Overall, 1127 patients experienced an AE (198.7 nE/100 PYE), the majority of which were mild (132.6 nE/100 PYE). The most frequently reported AEs (≥5.0% of patients) were the same as in the PT, including viral upper respiratory tract infection (18.2 nE/100 PYE, mainly reported as the common cold), atopic dermatitis (17.9 nE/100 PYE), upper respiratory tract infection (5.8 nE/100 PYE), headache (4.4 nE/100 PYE) and conjunctivitis (3.8 nE/100 PYE). The rates of AEs were generally lower as compared to short-term rates in the PT. Most of the serious AEs (SAEs; 4.9 nE/100 PYE) were reported as single events without clustering on the type. No events of conjunctivitis AEs were SAEs, and only five patients discontinued due to conjunctivitis AEs. AESI eye disorders, skin infections requiring systemic treatment, eczema herpeticum and malignancies were observed at rates similar to or lower than reported in PT. Consistent safety was demonstrated during up to 42 months of tralokinumab treatment in patients with moderate-to-severe AD. Exposure-adjusted incidence rates of AESIs, including eczema herpeticum and skin infections requiring systemic treatment, were generally lower than rates reported during the short-term, placebo-controlled period up to week 16. Exposure-adjusted incidence rates of conjunctivitis were lower with long-term exposure, and only five patients discontinued due to conjunctivitis. This analysis supports the long-term benefit-risk profile of targeted IL-13 inhibition with tralokinumab for patients with moderate-to-severe AD.